PENERAPAN LOCAL BASED CURRICULUM (LBC) PADA PEMBELAJARAN GEOGRAFI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI SISWA DI SMAN 1 X KOTO - Rima Refia Oktaviana; Nofrion (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the effect of implementing the Local Based Curriculum (LBC) on improving students’ Higher Order Thinking Skills (HOTS) in disaster mitigation material at SMAN 1 X Koto. This research employed a quantitative approach with a quasi-experimental method using a pretest-posttest control group design. The research sample consisted of an experimental class and a control class, each comprising 36 students. Data collection techniques included pretest, posttest, and HOTS quizzes. Data analysis was conducted using normality tests, homogeneity tests, Paired Sample T-test, Independent Sample T-test, and N-Gain analysis with the assistance of IBM SPSS 30. The results showed that there was a significant effect of implementing the Local Based Curriculum on improving students’ HOTS, with a significance value of 0.000 < 0.05. The results of the Independent Sample T-test showed a Sig. (2-tailed) value of 0.043 < 0.05, indicating a significant difference between the experimental and control classes. The average posttest score of the experimental class was 77.3, which was higher than the control class score of 72.1. The N-Gain value of the experimental class was 58.12%, categorized as moderately effective. Therefore, the implementation of the Local Based Curriculum was able to improve students’ Higher Order Thinking Skills in geography learning.